Jack Reacher : Bad Luck and Trouble - Book 11 - Child, Lee (New York : Dell, 2009)
When a man is killed by being thrown from a helicopter high over the California desert, Jack Reacher discovers that someone is targeting his old friends and teammates and launches a personal campaign to end the conspiracy.
Keywords: Reacher, Jack (Fictitious character) -- Fiction; Ex-police officers -- Fiction; Mercenary troops -- Fiction; Conspiracies -- Fiction; Male friendship -- Fiction; Interpersonal relations -- Fiction; Suspense